Genome Structures and Evolution Analysis of Hsp90 Gene Family in Brassica napus Reveal the Possible Roles of Members in Response to Salt Stress and the Infection of Sclerotinia sclerotiorum - Wang, Long; Liu, Fei; Ju, Lingyue; Xue, Bing; Wang, Yongfeng; Wang, Daojie; Hou, Dianyun (Frontiers in Plant Science, 2022)
Heat shock proteins 90 (Hsp90s) are conserved proteins participating in the responses to heat stress and are found to be involved in different kinds of abiotic and biotic stresses. Brassica napus (B. napus) is an important heteropolyploid crop, producing edible oil. Salt stress is one of the most important hazards to the growth of rape in the world, while Sclerotinia stem rot is one of the most serious diseases, caused by Sclerotinia sclerotiorum (S. sclerotiorum). In this study, the evolution of Hsp90 genes and their responses to these two stresses were elucidated. Bioinformatic analysis through the whole genome of B. napus identified 35 Hsp90 gene family members. Five groups were obtained via phylogenetic analysis with the 35 Hsp genes, Hsps from its two ancestor species Brassica rapa, Brassica oleracea, and AtHsps. Gene structure and conservative motif analysis of these 35 Hsps indicated that the Hsps were relatively conservative in each group. Strong collinearity was also detected between the genomes of Brassica rapa, Brassica oleracea and B. napus, along with identifying syntenic gene pairs of Hsps among the three genomes. In addition, whole genome duplication was discovered as the main reason for the generation of BnHsp gene family. The analysis of cis-acting elements indicated that BnHsp90 might be involved in a variety of abiotic and biotic stress responses. Analysis of the expression pattern indicated that BnHsp90 participates in the responses of B. napus to salt stress and the infection of S. sclerotiorum. Fourteen and nine BnHsp90s were validated to be involved in the defense responses of B. napus against salt stress and S. sclerotiorum, respectively. Our results provide new insights for the roles of BnHsp90s in the responses of B. napus to salt stress and S. sclerotiorum.